2013
DOI: 10.1371/journal.pone.0055213
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Regulates Rac1 Activation and Rat Pulmonary Microvascular Endothelial Hyperpermeability Induced by TNF-α

Abstract: A multiplicity of vital cellular and tissue level functions are controlled by caveolin-1 and it is considered to be an important candidate for targeted therapeutics. Rac1-cortactin signaling plays an important role in maintaining the functions of the endothelial barrier in microvascular endothelial cells. The activity of Rac1 has been shown to be regulated by caveolin-1. Therefore, the present study investigated the consequences of down-regulating caveolin-1 and the subsequent changes in activity of Rac1 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…Cav-1 associates with the hypervariable C-terminal domain of Rac1 through its scaffolding domain [24]. Cav-1 depletion led to the activation of Rac1 and consequently induced a Rac1 phenotype, increased cell spreading and loss of polarity [25][26][27]. In this present study, Cav-1 depletion increased Rac1 activity despite miR-199a-5p knockdown.…”
Section: Discussionsupporting
confidence: 58%
“…Cav-1 associates with the hypervariable C-terminal domain of Rac1 through its scaffolding domain [24]. Cav-1 depletion led to the activation of Rac1 and consequently induced a Rac1 phenotype, increased cell spreading and loss of polarity [25][26][27]. In this present study, Cav-1 depletion increased Rac1 activity despite miR-199a-5p knockdown.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies in endothelial cells in culture have shown that TNF-α increases monolayer permeability within 1h to 5h [52,53,54,55,56], although sometimes permeability is studied for up to 24h [57] at which time the mechanisms leading to increased permeability may differ [58]. In the first hours, TNF-α causes MLC- and Rho-kinase-dependent actin stress fiber formation [51] in cultured endothelial cells.…”
Section: Platelet-activating Factor (Paf)mentioning
confidence: 99%
“…This response is mediated by Rho-kinase which has consequently been linked to the ensuing increase in permeability [54,59], although this mechanism was questioned in one study [52]. Besides Rho-kinase, the following signaling molecules have been implicated in the TNF-α induced permeability increase in vitro : P-Rex1/Rac1 [55,56], PKCα [60], p38 [54,61], NO derived from endothelial NOS [58,62] leading to formation of peroxynitrite [63], and tyrosine kinase-mediated phosphorylation of VE-cadherin [55,64]. Interestingly, despite the fact that monolayer permeability usually starts to increase earliest 1h after stimulation with TNF-α, many of the signalling events that have been linked to the increase in permeability reach their maximum within 5-20 minutes, such as the activation of RhoA [59], rac1 [55], MAP kinases [54], src kinase [64], the phosphorylation of VE-cadherin [55], and the inactivation of myosin phosphatase target subunit 1 [59].…”
Section: Platelet-activating Factor (Paf)mentioning
confidence: 99%
“…Furthermore, a previous study demonstrated that treatment with NSC-23766, which disturbs the Rac1-specific GEFs T-cell lymphoma invasion and metastasis 1 and Trio, also decreased TER and promoted intercellular gap formation (19). Our previous study also demonstrated that TNF-α-induced PMVECs barrier breakdown was, at least in part, mediated by Rac1 inactivation (20). In addition, as the majority of findings on the microvascular endothelium are in accordance with existing reports that macrovascular endothelial cells are negatively affected by constitutively inactive Rac1 mutants (9,18), it is well-established that Rac1 appears to improve endothelial barrier properties under resting conditions.…”
Section: Discussionmentioning
confidence: 78%